Risk factors for late reconnections after circumferential pulmonary vein isolation guided by lesion size index – Data from repeat invasive electrophysiology procedure - Mujović, Nebojša M.; Marinković, Milan M.; Marković, Nebojša; Kocijančić, Aleksandar; Kovačević, Vladan; Vučićević, Vera; Mujović, Nataša M.; Potpara, Tatjana S. (Frontiers in Cardiovascular Medicine, 2023)
Background Late reconnections (LR) of pulmonary veins (PVs) after wide antral circumferential ablation (WACA) using point-to-point radiofrequency (RF) ablation are common. Lesion size index (LSI) is a novel marker of lesion quality proposed by Ensite Precision mapping system, expected to improve PV isolation durability. This study aimed to assess the durability of LSI-guided PVI and the risk factors for LR of PVs. Methods The prospective study included 33 patients with paroxysmal atrial fibrillation (PAF) who underwent (1) the index LSI-guided WACA procedure (with target LSI of 5.5-6.0 for anterior and 5.0-5.5 for posterior WACA segments) and (2) the 3-month protocol-mandated re-mapping procedure in all patients, irrespective of AF recurrence after the index procedure. Ablation parameters reported by Ensite mapping system were collected retrospectively. The inter-lesion distance (ILD) between all adjacent WACA lesions was calculated off-line. Association between index ablation parameters and the LRs of PVs at 3 months was analyzed. Results The median patient age was 61 (IQR: 53–64) years and 55% of them were males. At index procedure, the first-pass WACA isolation rate was higher for the left PVs than the right PVs (64 vs. 33%, p = 0.014). In addition, a low acute reconnection rates were observed, as follows: in 12.1% of patients, in 6.1% of WACA circles, in 3.8% of WACA segments and in 4.5% of PVs. However, the 3-month remapping study revealed LR of PV in 63.6% of patients, 37.9% of WACA circles, 20.5% of WACA segments and 26.5% of PVs. The LRs were identified mostly along the left anterior WACA segment. Independent risk factors for the LR of WACA were left-sided WACA location (OR 3.216 [95%CI: 1.065–9.716], p = 0.038) and longer ILD (OR 1.256 [95%CI: 1.035–1.523] for each 1-mm increase, p = 0.021). The ILD of > 8.0 mm showed a predictive value for the LR of WACA, with the sensitivity of 84% and specificity of 46%. A single case of cardiac tamponade occurred following the re-mapping invasive procedure. No other complications were encountered. Conclusion Although the LSI-guided PVI ensures a consistent PVI during the index procedure, LRs of PVs are still common. Besides the LSI, the PVI durability requires an optimal ILD between adjacent lesions, especially along the anterior lateral ridge.